2010
DOI: 10.3354/dao02206
|View full text |Cite
|
Sign up to set email alerts
|

Immune response in Lutjanus erythropterus induced by the major outer membrane protein (OmpU) of Vibrio alginolyticus

Abstract: The outer membrane proteins (OMPs) of the marine aquatic animal pathogen Vibrio alginolyticus play an important role in the virulence of the bacterium and are potential candidates for vaccine development. In this study, the major 35.6 kDa OMP of V. alginolyticus was isolated by gel excision from the crude OMP fraction from V. alginolyticus. The sequence of the first 27 amino acid residues from the N-terminal end of the protein is ATV YKD GGT ELL VGG RVE FRG DFI GSD, which has high homology with OmpU proteins f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…They play multiple functions and roles that help bacteria survive, such as acting as antennae for environmental signals, adhesion for colonization and also as invasion mediators (Cai et al . ). OMPs extracted from some bacterial fish pathogens have been shown to be protective antigens, including V. alginolytiucs , V. anguillarum , V. harveyi , Aeromonas hydrophila , Aeromonas veronii , Aliivibrio salmonicida and Edwardsiella tarda in fish (Vazquez‐Juarez et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…They play multiple functions and roles that help bacteria survive, such as acting as antennae for environmental signals, adhesion for colonization and also as invasion mediators (Cai et al . ). OMPs extracted from some bacterial fish pathogens have been shown to be protective antigens, including V. alginolytiucs , V. anguillarum , V. harveyi , Aeromonas hydrophila , Aeromonas veronii , Aliivibrio salmonicida and Edwardsiella tarda in fish (Vazquez‐Juarez et al .…”
Section: Discussionmentioning
confidence: 97%
“…In a previous study, we reported that the isolated OmpU was a good protective antigen of f V. alginolyticus in L. erythropterus (Cai et al . ). It was also reported that the OmpU in V. cholerae V. fischeri and V. splendidus could provide significantly protection against corresponding pathogens (Das et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This result agreed with the protective effect of OmpU of V. alginolyticus and V. mimicus (Cai et al . ; Cen et al . ).…”
Section: Discussionmentioning
confidence: 99%